A STUDY OF THE FIFTH SEMESTER STUDENTS IN VOCABULARY KNOWLEDGE OF ENGLISH STUDY PROGRAM FKIP UNIVERSITAS RIAU - Muhammad Sahreza; Novitri Novitri; Syarfi Syarfi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The aim of this research is to find out the level of the fifth semester students of English Study Program FKIP Universitas Riau in vocabulary knowledge. The sample of this research is class 5C of the third year students of English Study Program which were choosen by using cluster random sampling technique. The number of the students is 37 students. The data obtained by giving multiple choice tests to students that is adapted by Paul Nation level test . The test asked the students to choose the appropriate vocabulary based on the context of the test. The test consist of 8 indicators of vocabulary. There are noun, verb, adjective, adverb, pronoun, synonym, antonym and context clues. The result shows that the students score in vocabulary knowledge is 68.1, and the students have problem in antonym with mean score 39,45 % of correct answers. In conclusion, from the result above shows that the students vocabulary knowledge level of FKIP Universitas Riau is in good level but having problem in finding antonym.Key Words: Study, Vocabulary,Knowledge